Design of Steel Bearing Plates - Fling, Russell S. (Engineering Journal, 1970)
Base plates for columns and bearing plates for beams resting on masonry are details associated with the design of all steel structures. Given the load and allowable bearing pressure, the area of the plate is easily computed. From this, the overhanging cantilever span can be determined. If the yield point of the steel is known, the thickness of the plate required can be determined by the procedures outlined on pages 2-44 or 3-75 of the AISC Manual. This solution is time consuming if more than an occasional bearing plate is encountered. Fortunately it can be easily presented in tabular or graphical form. Design procedures presented in the AISC Manual are silent on two important questions. No limit is placed on plate deflections. Column base plates nearly the same size as the column cannot be properly designed by the AISC procedures.